ASSESSMENT OF KNOWLEDGE AND PRACTICE OF CHILD CARE AMONG MOTHERS OF ONE TO THREE YEARS CHILDREN IN A SELECTED RURAL AND URBAN COMMUNITY. KOLKATA, WEST BENGAL - Dutta, Krishna (International Journal of Research -GRANTHAALAYAH, 2023)
The investigator conducted a comparative descriptive study to assess Knowledge and Practice of Childcare among Mothers of One to Three years children in a selected rural and urban community. Kolkata, West Bengal. She selected 50 rural mothers and 50 urban mothers using non-probability purposive sampling technique. The conceptual framework is based on Barnard Child health assessment model. Semi Structured and structured interview schedule used for data collection. Result showed that mean knowledge score between rural mothers and urban mothers statically significant as evidenced by calculated‘t’ value 11.42 at 0.05 level of significance . The difference of mean Practice score between rural mothers and urban mothers statically significant as evidenced by calculated‘t’ value 13.75 at 0.05 level of significance. There was relationship between knowledge and practice (0<0.67<1) and (0<0.71<1), in rural and urban community, respectively. The findings of study have implications in the field of Community Health Nursing, Nursing Administration and Nursing Research.